THE DEVELOPMENT OF MARKET ORIENTED CROP PRODUCTION AS A FACTOR IN REDUCING RURAL POVERTY IN SERBIA - Stevanović, Simo; Đorović, Milutin T. (Economics of Agriculture, 2011)
This paper analyses the development of market orieneted production of major crop products by districts in 2009, in order to reduce rural poverty in the Republic of Serbia. Similarities in analyzed characteristics between districts are presented by the method of complete linkage hierarchical cluster analysis (agglomerative hierarchical clustering), whose results are shown by a dendogram. Production of wheat and maize in the Republic of Serbia, especially in Vojvodina is characterized by a high degree of marketability. In addition to the favorable climate, fertile land and traditional production practices, largely contributed to the high prevalence of these crops in the agricultural production structure in Vojvodina. The proximity of processing capacities and their concentration in Vojvodina are crucial for the presence of sugar beet and sunflower in the crop production structure of the Serbia. Due to high household consumption, production of beans and potatoes have a lower marketability than other crops analyzed. The high prevalence of traditional methods of intercropping beans with maize, further contributed to the low marketability of this producs in the Serbia.The possibility of growing potatoes at high altitudes, as compared to other crops, resulted in specialization among producers and concentration of production in the southwestern districts in central Serbia. According to the OECD methodology, the territory of the Serbia, is predominantly rural (18 out of 25 districts are rural), in addition to the Belgrade district, which is predominantly urban, there are 6 districts that are transient. Bearing this fact in mind, increase in the level of marketability of crop and agricultural products will surely reduce rural poverty in Serbia.